2004
DOI: 10.1177/0020872804043958
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Role of the Hospital Social Worker in Australia

Abstract: This study assessed the role of the hospital social worker during the hospital stay and post-discharge period. Findings revealed that social workers performed various tasks, and the most common concerns of patients were coping and/or post-discharge issues. Findings also demonstrated the complexity of this role in meeting the needs of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 19 publications
0
15
1
2
Order By: Relevance
“…Även forskning kring skolkuratorers relation till andra yrkesgrupper i skolan som skolpsykologer och studie-och yrkesvägledare beskrivs i studier av Altshuler & Webb (2009), Gibelman (1993) och Agresta (2004Agresta ( , 2006. Davis, Milosevic, Baldry & Walsh (2004) har undersökt en annan socionomgrupp som arbetar i en organisation som domineras av andra yrkesgrupper, nämligen sjukhuskuratorer, och visar att den medicinska personalen och sjukhuskuratorerna har olika uppfattningar både vad gäller kuratorns roll och arbetsuppgifter. Flera av sjukhuskuratorns arbetsuppgifter delas med sjuksköterskor, t.ex.…”
Section: Tidigare Forskningunclassified
See 1 more Smart Citation
“…Även forskning kring skolkuratorers relation till andra yrkesgrupper i skolan som skolpsykologer och studie-och yrkesvägledare beskrivs i studier av Altshuler & Webb (2009), Gibelman (1993) och Agresta (2004Agresta ( , 2006. Davis, Milosevic, Baldry & Walsh (2004) har undersökt en annan socionomgrupp som arbetar i en organisation som domineras av andra yrkesgrupper, nämligen sjukhuskuratorer, och visar att den medicinska personalen och sjukhuskuratorerna har olika uppfattningar både vad gäller kuratorns roll och arbetsuppgifter. Flera av sjukhuskuratorns arbetsuppgifter delas med sjuksköterskor, t.ex.…”
Section: Tidigare Forskningunclassified
“…Flera av sjukhuskuratorns arbetsuppgifter delas med sjuksköterskor, t.ex. rådgivning och stöd, och rollfördelningen är ofta otydlig (Davis et al 2004).…”
Section: Tidigare Forskningunclassified
“…undertaken using daily statistics collected by social workers in a public hospital in Australia (for a description of the Australian health care context see the first part of this study, Davis et al, 2004). Findings revealed that social workers spent more time on direct patient activities than departmental or administrative tasks.…”
mentioning
confidence: 97%
“…However, Egan and Kadushin (1995) found that social workers felt they were "better qualified than nurses to assess and intervene in social and emotional problems" (p. 3), while discharge planning is generally seen to be a social work responsibility. Davis et al (2004) observed that despite discharge planning usually being seen as part of social work' s primary role in hospital settings, social workers in their study spent more time on assessments, counselling activities, and liaison work. In general, Egan and Kadushin found substantial similarity in how social workers and nurses defmed the social work role in the hospital setting, with many psychosocial tasks viewed as joint role responsibilities.…”
Section: Delineation Of Roles In Hospital Social Workmentioning
confidence: 90%
“…Rural hospitals or those experiencing budget shortfalls may be especially susceptible to lack of role clarity (Egan & Kadushin), while simple lack of awareness of the important range of social work activities may result in the role being devalued (Auerbach et al). According to Davis, Baldry, Milosevic, and Walsh (2004), confusion about roles can also lead to lack of accountability within the organization, duplication of services, or services not being provided when needed.…”
Section: Delineation Of Roles In Hospital Social Workmentioning
confidence: 99%